Seismic site classification based on constrained modeling of measured HVSR curve in regolith sites. Issue 110 (July 2018) - Setiawan, Bambang; Jaksa, Mark; Griffith, Michael; Love, David
Abstract: Seismic site classification is the most widely accepted practical method in the design of seismic resistant infrastructure. The horizontal vertical spectral ratio (HVSR) technique for analyzing ambient noise data has been successfully applied to quantify site effects in the estimation of seismic site classes associated with seismic hazards. This successful application was mainly carried out in high impedance contrast sites. The present paper focuses on the application of the HVSR technique to regolith sites which were suggested by previous studies to be low in impedance contrast between the upper and underlying bedrock layers (< 4–5). A case study is examined which explores the central business district of Adelaide, South Australia and incorporates 10 in situ ambient noise measurements carried out across the city. Adelaide experienced more medium-sized earthquakes than any other capital city in Australia in the past half of the last century. Site amplification was also observed to occur in Adelaide. Ambient noise data were used to estimate the site predominant period and to infer the site shear wave profile, after establishing that the data were free from noises from an industrial source, checking the reliability of the HVSR ellipticity curve and validating the appropriateness of the adopted method and resulting shear wave models. The results show that the predominant fundamental period for Adelaide is 0.8 s or higher, which suggests a subsoil class D according to the Australian Standard. Results of the inversion for the upper 30 m shear wave velocities of Adelaide's subsoil layers varies from 194 m/s to 418 m/s, which are related to classes D to C (NEHRP classification system), classes D to B (Australian Standard classification system) or classes D/DE to C (regolith case classification system). These results are in a good agreement with several previous studies. This suggests a promising application of the HVSR analysis for seismic assessment at regolith sites. Highlights: The application of the HVSR technique to regolith sites which were suggested to be various in impedance contrast between the upper and underlying bedrock layers is investigated. A case study is examined which explores the central business district of Adelaide, South Australia and incorporates 10 in situ ambient noise measurements carried out across the city. A better resolution seismic site classification at the central business district of Adelaide, South Australia is proposed. A promising application of the HVSR analysis for seismic assessment at regolith sites is presented.